Renewable energy sources from biomass through incineration - Rozainee, M.; Ngo, S.P; Salema, A. A.; Tan, K.G. (Board of Engineers Malaysia, 2008)

(untitled)
The new five-fuel policy proposed by the Economic Planning Unit of the Malaysian Prime Minister’s Department, targets to achieve 5% electricity production from renewable energy sources to complement the current four-fuel policy of natural gas, coal, petroleum and hydroelectricity. Of particular interest are rice husk and palm wastes (fibre, shell and empty fruit bunch) with annual generation rates of 0.47 million tonnes (as of 2001) and 18.8 million tonnes(as of 2001)respectively. Apart from solving its disposal problems, energy recovery through combustion of rice husk results in the formation of ash that has high commercial value due to its high silica content. Palm wastes, on the other hand, are produced in quantities exceeding the internal energy requirements for palm oil mills. Realising the good potential of the fluidised bed technology in recovering energy from biomass, extensive research in the combustion of biomass using the fluidised bed technology is currently being carried out at Universiti Teknologi Malaysia(UTM). Different variants of the fluidised bed technology, namely the conventional bubbling fluidised bed, spouted bed(SB) and spinning fluidised bed(SFB) are being explored with the focus on the combustion of rice husk and palm wastes. This paper presents some of the results achieved from the research programmes.